Comprehensive ecological and biological assessment of soils of a medium-sized city in the Central Federal District, Russia - A. G. Kosmacheva; T. A. Trifonova; A. A. Martsev; O. G. Selivanov; A. O. Rostunov (Трансформация экосистем)
The ecological and biological state of the soil cover has been assessed comprehensively in the typical medium-sized industrial city of Gus-Khrustalny (population of up to 100000) in the Vladimir Oblast, Central Federal District, Russia. The results obtained demonstrate the heterogeneity of the soils in terms of organic matter content (0–10.22%), the activity of catalase (0.26–2.71 mL O2 /(min × g)) and urease (0–0.69 mg NH3 /(10 g of soil × 24 h)), and the integral indicator of the ecological and biological state of the soil (39.13–100%). The studied samples are characterized as ‘poor’ and ‘very poor’ in terms of catalase activity and as ‘very poor’ in terms of urease activity. The indices of enzymatic activity were more sensitive to changes in soil properties in comparison with plant testing methods. A strong uneven anthropogenic impact on urban soils is detected, changing soil biological indices and resulting in the soil cover heterogeneity in urbanized areas.